Erysiphe dudkae sp. nov., a new species of powdery mildews on Brugmansia suaveolens (Solanaceae) from Montenegro - Heluta, V.P. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2014)
A new species, Erysiphe dudkae V.P. Heluta, sp. nov. (Ascomycota, Erysiphales), on Brugmansia suaveolens (Humb. et Bonpl.
ex Willd.) Bercht. et J. Presl (Solanaceae) is described. The fungus was collected by Irina O. Dudka in 2013 in Montenegro in
two localities. It belongs to the section Microsphaera (Lév.) U.
Braun et Shishkoff. Morphologically, E. dudkae is very similar
to E. ornata var. europaea (U. Braun) U. Braun et S. Takam.
parasitizing birch, but differs from it primarily by the shape of
appendages. In E. dudkae, appendages are horizontal or slightly
raised, with straight or somewhat curved stalks, while in E. ornata
var. europaea stalks are very curved, so that appendages are almost
vertical. Описується новий для науки вид Erysiphe dudkae V.P. Heluta, sp. nov. (Ascomycota, Erysiphales), що розвивається на Brugmansia suaveolens (Humb. et Bonpl. ex Willd.) Bercht. et J. Presl (Solanaceae). Він знайдений І.О. Дудкою в 2013 р. в Чорногорії у двох локалітетах. Гриб належить до секції Microsphaera (Lév.) U. Braun et Shishkoff. Морфологічно E. dudkae дуже близький до E. ornata var. europaea (U. Braun) U. Braun et S. Takam. – паразита представників роду Betula L., однак відрізняється від нього насамперед формою придатків. У E. dudkae вони горизонтальні чи дещо піднімаються, з прямими або ж слабо зігнутими стержнями, тимчасом як у E. ornata var. europaea придатки мають дуже зігнутий стержень, унаслідок чого вони майже вертикальні. Описывается новый для науки вид Erysiphe dudkae V.P. Heluta, sp. nov. (Ascomycota, Erysiphales), который развивается на Brugmansia suaveolens (Humb. et Bonpl. ex Willd.) Bercht. et J. Presl (Solanaceae). Он найден И.А. Дудкой в 2013 г. в Черногории в двух локалитетах. Гриб принадлежит к секции Microsphaera (Lév.) U. Braun et Shishkoff. Морфологически E. dudkae очень близкий к E. ornata var. europaea (U. Braun) U. Braun et S. Takam. – паразиту представителей рода Betula L., однако отличается от него прежде всего формой придатков. У E. dudkae они горизонтальные или же несколько приподнимающиеся, с прямыми или же слабо согнутыми стержнями, в то время как у E. ornata var. europaea придатки имеют сильно согнутый стержень, вследствие чего они почти вертикальные.